Enhanced Recovery After Surgery in Patients With Hepatocellular Carcinoma Undergoing Laparoscopic Hepatectomy - Zhou, Jiamin; He, Xigan; Wang, Miao; Zhao, Yiming; Zhang, Ning; Wang, Longrong; Mao, Anrong; Wang, Lu (Frontiers in Surgery, 2021)
Objective: To compare the effectiveness and safety of enhanced recovery after surgery (ERAS) in patients with hepatocellular carcinoma (HCC) undergoing laparoscopic hepatectomy. Methods: From September 2016 to June 2019, 282 patients were enrolled, and ERAS was implemented since March 2018. All indicators related to surgery, liver function, and postoperative outcomes were included in the analysis. Propensity score matching (PSM) identified 174 patients for further comparison. Results: After PSM, the clinicopathological baselines were well matched. The ERAS group showed significantly less intraoperative blood loss (100.00 [100.00-200.00] ml vs. 200.00 [100.00-300.00] ml, P = 0.001), fewer days before abdominal drainage tube removal (4.00 [3.00-4.00] days vs. 4.00 [3.00-5.00] days, P = 0.023), shorter hospital stay after surgery (6.00 [5.00-6.00] days vs. 6.00 [6.00-7.00] days, P <0.001), and reduced postoperative morbidity (18.39% vs. 34.48%, P = 0.026). The proportion of patients with a pain score ≥ 4 was significantly lower in the ERAS group within the first 2 days after surgery (1.15% vs. 13.79% and 8.05% vs. 26.44%, P = 0.002 and P = 0.001, respectively). Pringle maneuver was performed more frequently in the ERAS group (70.11% vs. 18.39%, P < 0.001) and a significantly higher postoperative alanine aminotransferase level was also observed (183.40 [122.85-253.70] U/l vs. 136.20 [82.93-263.40] U/l, P = 0.026). The 2-year recurrence-free survival was similar between the two groups (72% vs. 71%, P = 0.946). Conclusions: ERAS programs are effective and safe in the perioperative period and do not influence mid-term recurrence in HCC patients undergoing laparoscopic hepatectomy.